Is it Safe to Reopen Theaters During the COVID-19 Pandemic? - Liang, Chenjiyu; Jiang, Sihang; Shao, Xiaoliang; Wang, Huan; Yan, Shuai; Yang, Zixu; Li, Xianting (Frontiers in Built Environment, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is spreading globally, and its high transmission speed and mortality rate are severely interfering with people's normal lives and the economy. Governments are now reopening their economies; however, the opening of theaters has been delayed, owing to their (often) crowded audiences and potentially higher infection risk. To determine whether it is safe to reopen theaters, in this study, the transport of contaminants released by an infected person in a theater hall with an overhead air supply system is analyzed numerically. The infection risks are calculated for occupants at various distances from the infected person in different directions and with/without wearing masks based on a revised Wells-Riley model, and under different supply air states and locations of the infected person. The results show that, first, the probabilities of infection in return air with filtration and all-fresh-air operations are decreased by 39.8% and 55.6%, respectively, as compared when the return air is not filtered. Second, the probabilities of infection for audiences sitting nine seats away from the infected person on the right, right-back, and back sides are 84.9%–92.3%, 37.3%–74.0%, and 36.3%–72.0% lower, respectively, than those for audiences sitting one-seat away from the infected person. In addition, sitting in separate rows can reduce the maximum probability by 7.4%-68.3%. Third, the probability of infection can be reduced by 93.7% after all the audiences wear masks with efficiencies of 75%. Fourth, the probability of infection can be controlled under a relatively safe range even though the quanta emission rate is 30 or 50 quanta/h, and even with two infected people in unfavorable seats. Thus, theaters can be safely reopened under return air filtration or all fresh air operations, and when audiences are sitting in separate seats and wearing masks.